2009
DOI: 10.1111/j.1467-9841.2009.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

On ‘flip‐flopping’: Branded stance‐taking in U.S. electoral politics1

Abstract: This article examines stance in U.S. political discourse, taking as its empirical point of departure Democratic candidate John Kerry's epistemic stance‐taking in the televised 2004 presidential debates. Kerry's stance‐taking is shown to help display the characterological attribute of ‘conviction’ and serve as a rejoinder to critics who had branded him as a ‘flip‐flopper.’ His stance‐taking is thus not primarily ‘to’ or ‘for’ copresent interactants, but is largely interdiscursive in character. ‘Conviction’ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…Stance is a public act by a social actor, achieved dialogically through overt communicative means, of simultaneously evaluating objects, positioning subjects (self and others), and aligning with other subjects, with respect to any salient dimension of the sociocultural field. (Du Bois 2007: 163) Michael Lempert (2009) analyzes American politicians' stance-taking across broad discursive fields, beyond any particular communicative event. Lempert is particularly interested in the notions of "conviction" versus "flip-flopping" in US politics, and how judgments about these attributes relate to stance-taking in multiple speech events over time.…”
Section: Discussionmentioning
confidence: 99%
“…Stance is a public act by a social actor, achieved dialogically through overt communicative means, of simultaneously evaluating objects, positioning subjects (self and others), and aligning with other subjects, with respect to any salient dimension of the sociocultural field. (Du Bois 2007: 163) Michael Lempert (2009) analyzes American politicians' stance-taking across broad discursive fields, beyond any particular communicative event. Lempert is particularly interested in the notions of "conviction" versus "flip-flopping" in US politics, and how judgments about these attributes relate to stance-taking in multiple speech events over time.…”
Section: Discussionmentioning
confidence: 99%
“…While his lack of clear statements may not have opened Hatoyama to charges of flip-flopping (a charge commonly made in the US) per se, his uncertain stance nonetheless failed to signal conviction (Lempert 2009) or message (Hill 2001). On the issue of the Futenma replacement facility, Hatoyama would later suggest that his personal preference had been to remove the new base to Guam, and that he later concluded that placement in Kagoshima prefecture, Japan, would be a proper compromise (Kyodo 2009, June 11).…”
Section: Discussionmentioning
confidence: 99%
“…(Du Bois 2007: 163) Michael Lempert (2009) analyzes American politicians' stance-taking across broad discursive fields, beyond any particular communicative event. Lempert is particularly interested in the notions of "conviction" versus "flip-flopping" in US politics, and how judgments about these attributes relate to stance-taking in multiple speech events over time.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, Stivers appears to be more concerned with the participants' distinction between affiliation and alignment (2008, p. 36), while my focus is on distinguishing different ways in which non-alignment is deployed and interpreted. 6 For alternative views on stance, see also Goodwin (1998Goodwin ( , 2006, Kiesling (2005), Johnstone (2009), Lempert (2008Lempert ( , 2009), Ochs and Schieffelin (1989). 7 However, Du Bois focuses mostly on agreement (all but one of his examples in the article are of agreement) and he uses the words ''alignment'' and ''agreement'' interchangeably.…”
mentioning
confidence: 97%